2020
DOI: 10.3951/biomechanisms.25.151
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Anatomical Structure of the Gluteus Medius and its Function in Walking

Abstract: The gluteus medius muscle is an important muscle that dampens and stabilizes the lateral inclination of the pelvis during one-leg standing and walking. Defining the internal structure of the gluteus medius muscle, muscle output and electromyographic waveform characteristics leads to appropriate improvement of the examination method in clinical practice and better interpretation of the examination data, and can contribute to improvement and prevention of functional disorders such as instability and fall.Macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In particular, the number and location of the fiber bundles is controversial. Some studies have reported three fiber bundles segments (anterior, middle and posterior) [9][10][11] , while others have reported two (anterior and posterior) 12,13) . Moreover, quantitative information on the borders of the fiber bundles has not been provided in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the number and location of the fiber bundles is controversial. Some studies have reported three fiber bundles segments (anterior, middle and posterior) [9][10][11] , while others have reported two (anterior and posterior) 12,13) . Moreover, quantitative information on the borders of the fiber bundles has not been provided in these reports.…”
Section: Introductionmentioning
confidence: 99%